Peningkatan Kompetensi Amil Organisasi Pengelola Zakat (OPZ) melalui Pelatihan Akuntansi Syariah: Improving the Amil Competence of Zakat Management Organizations through Sharia Accounting Training - Falikhatun, Falikhatun; Wahyuni, Salamah; Tirtoprojo, Susanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This Community Service (PkM) aims to increase Amil's competency in preparing Financial Reports by PSAK 109 and PSAK 112. The method used in this service is training for Amil from the Zakat Management Organization (ZMO), totaling 17 people. This training began with a pre-test to measure Amil's initial understanding of recording transactions and preparing financial reports, continued with the presentation of material, questions, and answers, and practice analyzing cases related to zakat, Infaq, Shadaqah, waqf funds, and ended with a post-test. The results of this service show that the training participants understand the differences in the concepts of zakat, infaq, shadaqah, and waqf, as well as the types of OPZ financial reports and the function of each financial report.